Synthesis of New 5-Oxazolones: Their Ring Opening Reactions to Obtain New Benzamide Derivatives - Tahir Gunkara, Omer; Guleli, Muge; Akkus Cevikkalp, Senem; Kaya, Kerem; Ocal, Nuket (Current Organic Synthesis, 2017)
New 5-oxazolones have been synthesized via N-protected amino acids which were prepared from various aryl acyl halides and L-amino acids, with DCC. Then, we studied the ring opening reactions of 5-oxazolones with nucleophilic attack by primary aryl amines to obtain new racemic benzamide derivatives. All new synthesized compounds have been characterized by FTIR, 1H, 13C NMR, GC/MS, LC/MS and Qtof analyses. X-Ray results of N-(1-((4-chlorophenyl)amino)-3-methyl-1-oxopentan-2-yl)-3-(trifluoromethyl)benzamide clearly showed absolute stereostructure.
Keywords: nucleophilic attack